The didactic phenomenon: deciphering students' learning obstacles in set theory - Hendriyanto, Agus; Suryadi, Didi; Juandi, Dadang; Dahlan, Jarnawi Afgani; Hidayat, Riyan; Wardat, Yousef; Sahara, Sani; Muhaimin, Lukman Hakim (Sriwijaya University, 2024)
Teachers play a crucial role in disseminating knowledge in educational settings, typically adhering to a credulist-testimonial approach outlined in pedagogical literature. Consequently, students often acquire knowledge through this method, potentially leading to discrepancies between their conceptual understanding and the intended educational objectives. This study investigates the phenomenon of learning obstacles encountered by junior high school students, with a particular emphasis on mathematics education. It is part of a series of Didactical Design Research (DDR) projects aimed at developing effective instructional materials. Employing an interpretive paradigm within the DDR framework, the study adopts a qualitative approach utilizing hermeneutic phenomenology design. Various research tools such as diagnostic assessments, interview guidelines, observation sheets, and audio recordings are employed. Data analysis is conducted using the Constant Comparative Method (CCM). The findings highlight ontogenic, didactic, and epistemological obstacles students face, stemming from factors such as a lack of interest in mathematics, ineffective material presentation, and misconceptions regarding set concepts. These results underscore the importance of educators employing effective teaching strategies to help students overcome these obstacles and succeed in their mathematics lessons.